Antimicrobial properties of Euphorbia hirta crude extract - Jusoh, Ahmad Fadly (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2006)
Antimicrobial effects from the extracted whole plant of Euphorbia hirta were studied against several Gram positive and Gram negative bacteria. Water and petroleum ether fraction of the extract have been isolated by using the soxhet extraction method. The Minimum Inhibitory Concentration (MIC) tests were done to determine the minimum concentration of the crude extract that can inhibit bacterial growth. The minimum inhibitory concentration of both extract are 25.00 mg/ml (water extract) and 0.025 mg/ml (petroleum ether extract) respectively. Agar diffusion test was also done by impregnating different concentration of the water extract- 100 mg/ml, 50 mg/ml, 25 mg/ml and the petroleum ether extract- 0.1 mg/ml, 0.05 mg/ml, 0.025 mg/ml respectively onto the standard blank disc. Significant inhibition zone were observed with 0.1 mg/ml of petroleum ether fraction against methicillin resistant Staphylococcus aureus (MRSA), Staphylococcus aureus (ATCC 25923) and Staphylococcus epidermidis on a nutrient agar plates. However, no inhibition zones were observed against the Gram negative bacterial plates consisted of Escherichia coli (ATCC 25922) and Salmonella sp. for both extracts. This result however, primarily validates that the petroleum ether Euphorbia hirta crude extract has shown to be a promising effective antibacterial agents against certain Gram positive bacteria.